Cancer‐specific and net overall survival in older patients with de novo metastatic prostate cancer initially treated with androgen deprivation therapy. (25th May 2022) - Narita, Shintaro; Terada, Naoki; Nomura, Kyoko; Sakamoto, Shinichi; Hatakeyama, Shingo; Kato, Takuma; Matsui, Yoshiyuki; Inokuchi, Junichi; Yokomizo, Akira; Tabata, Ken‐ichi; Shiota, Masaki; Kimura, Takahiro; et al.
Abstract : Objective: This study aimed to assess survival outcomes in older patients with de novo metastatic prostate cancer who initially received androgen deprivation therapy. Methods: The retrospective multicenter study included 2784 men with metastatic prostate cancer who were treated with androgen deprivation therapy between 2008 and 2017. Patients were classified into <75, 75–79, and ≥80 age groups. Propensity score matching was conducted to assess the cancer‐specific survival of the groups. The 5‐year net overall survival of each group was derived to evaluate relative survival compared with the general population using the Pohar–Perme estimator and the 2019 Japan Life Table. Results: During the follow‐up (median, 34 months), 1014 patients died, of which 807 died from metastatic prostate cancer progression. Compared with the <75 group, the cancer‐specific survival of the 75–79 group was similar (hazard ratio 1.07; 95% confidence interval 0.84–1.37; P  = 0.580), whereas that of the ≥80 group was significantly worse (hazard ratio 1.41; 95% confidence interval 1.10–1.80; P  = 0.006). The 5‐year net overall survival of the <75, 75–79, and ≥80 age groups were 0.678, 0761, and 0.718, respectively. The 5‐year net overall survival of patients aged ≥80 years with low‐ and high‐volume disease were 0.893 and 0.586, respectively, which was comparable with those in patients aged <75 years (0.872 and 0.586, respectively). Conclusions: Older metastatic prostate cancer patients aged ≥80 years had poorer cancer‐specific survival compared with younger patients. Conversely, 5‐year net overall survival in older patients aged ≥80 years was comparable with that in younger patients aged <75 years.